2012
DOI: 10.1021/ic301746c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Amine-Bridged Bis(phenolate)lanthanide Alkoxides and Their Application in the Controlled Polymerization of rac-Lactide and rac-β-Butyrolactone

Abstract: A series of neutral lanthanide alkoxides supported by an amine-bridged bis(phenolate) ligand were synthesized, and their catalytic behaviors for the polymerization of rac-lactide (LA) and rac-β-butyrolactone (BBL) were explored. The reactions of (C(5)H(5))(3)Ln(THF) with amine-bridged bis(phenol) LH(2) [L = Me(2)NCH(2)CH(2)N{CH(2)-(2-OC(6)H(2)Bu(t)(2)-3,5)}(2)] in a 1:1 molar ratio in THF for 1 h and then with 1 equiv each of 2,2,2-trifluoroethanol, benzyl alcohol, and 2-propanol gave the neutral lanthanide al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 85 publications
(21 reference statements)
1
50
1
Order By: Relevance
“…Based on the excellent catalytic properties for lactide polymerization catalyzed by wellcharacterized rare-earth metal complexes [12][13][14][15][16], amine-bis(benzotriazole phenolate) dysprosium and yttrium complexes 1-6 are expected to behave as air-stable catalysts for ROP of lactide (LA).…”
Section: Ring-opening Polymerization Of Lactidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the excellent catalytic properties for lactide polymerization catalyzed by wellcharacterized rare-earth metal complexes [12][13][14][15][16], amine-bis(benzotriazole phenolate) dysprosium and yttrium complexes 1-6 are expected to behave as air-stable catalysts for ROP of lactide (LA).…”
Section: Ring-opening Polymerization Of Lactidesmentioning
confidence: 99%
“…reported group 3 metal catalysts featuring diamine-bis(phenolate) ligands, and these lanthanide alkoxides (metal = Yb or Er) were found to display not only outstanding performances but also the highest stereoselectivity (P r = 0.99) for heteroselective polymerization of rac-LA [14][15][16]. These group 3/rare-earth catalytic systems with bis(phenolate) ligands gave advantages of good activity, excellent controllability and high heterotactic selectivity of lactide polymerization.…”
Section: Introductionmentioning
confidence: 98%
“…Overall, THF is the optimal solvent, which is consistent with reported results. 24 Almost quantitative yields were obtained with the ratio of monomer to complex 1 increasing from 300 to 1200 (Table 3, entries 4-7). A good yield of 84% was still obtained when the ratio was increased to 1500.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the carbon-bridged bis(phenolate) lanthanide alkoxo complexes are efficient initiators for the controlled polymerization of ε-caprolactone [17]. The lanthanide aryloxides and alkoxides stabilized by amine bridged bis(phenolate) ligand are efficient initiators for the stereoselective controlled polymerization of rac-lactide and rac-bbutyrolactone [13,15]. Cationic amidozirconium and titanium complexes bearing an amine-bridged bis(phenolato) ligand are highly efficient catalysts for regioselective intermolecular hydroamination reactions of various terminal alkynes and anilines, with good to excellent yields and 100% Markovnikov selectivity [18].…”
mentioning
confidence: 99%